AKTIVITAS ANTIHIPERURIKEMIA EKSTRAK ETIL ASETAT DAN ETANOL BUAH SALAK VARIETAS BONGKOK (Salacca edulis Reinw.) PADA TIKUS GALUR WISTAR [Antihyperuricemic Activity of Ethyl Acetate and Ethanol Extracts of Snake Fruit var. Bongkok (Salacca edulis Reinw.) o - Leni Herliani Afrianti; Elin Yulinah Sukandar; I Ketut Adnyana; Slamet Ibrahim - (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The aims of the study was to determine antihyperuricemic activity of ethyl acetate and ethanol extractsof snake fruit (Salacca edulis Reinw.) var. Bongkok on Wistar male rats. Wistar male rats administered with 100 and 200 mg/kg b.w ethyl acetat extract and 200 mg/kg b.w ethanol extract and simulationsly induced with potassium oxonate peritoneally and uric acid orally showed descreased uric acid serum level significantly as compared to control group at 6th and 7thhour (p < 0.05). Meanwhile ethanol extract at 100 mg/kg bw did not affect uric acid serum level significantly. Determination of uric acid level in urine of the rats, indicated that administration ofethanol extract at 200 mg/kg bw, orprobenecid as a standard at 45 mg/kg bw, increased excretion of urine uric acid level significantly as compared to control group at 7thhour (p < 0.05). Additionally, administration of ethyl acetate extract at 100 and 200 mg/kg bw did not show an increase of uric acid excretion in urine. Mechanism of action of the ethyl acetate extract and ethanol extract as an antihyperuricemic agent has been proposed by inhibition of xanthine oxidase activity wich decrease the synthesis of uric acid. Hence, the mechanism of action of antihyperuricemia of the ethanol extract was suggested to be an uricosuric i.e. increases the excretion of urine uric acid and xanthine oxidase inhibitory.